Tumoral Calcinosis of Thoracic Spine Associated with Vertebral Fracture and Inflammatory Reactions - Isamu Miura; Motoo Kubota; Kento Takebayashi; Oji Momosaki; Koichi Honma; Takakazu Kawamata; Masahito Yuzurihara (Case Reports in Orthopedics)
Tumoral calcinosis involving the spine is rare. The involvement of the thoracic spine is rarer than that of the cervical or lumbar spine. We report a case of thoracic tumoral calcinosis accompanied by vertebral fracture with increased concentrations of inflammatory markers and no abnormalities in serum calcinosis and phosphorus concentration. A 60-year-old woman presented with complete paraplegia. Her white blood cell count and C-reactive protein (CRP) concentration were elevated. The thoracic magnetic resonance imaging revealed vertebral fracture and an epidural mass that demonstrated low intensity on both T2- and T1-weighted images at the T9/10 dorsal side of the central canal. This lesion is larger in size than that observed in the previous 2 months. Her laboratory data showed signs of infection, and only decompression surgery without fixation for treatment and diagnosis was performed. Histopathological examination was consistent with tumoral calcinosis. Postoperatively, the patient’s white cell count and CRP concentration were normalized. We found that tumoral calcinosis can occur at the thoracic level on the basis of the spinal instability due to the vertebral compression fracture and the accompanying increase in inflammation indicated by increased white blood cell count and CRP concentration.